2022
DOI: 10.1108/jfra-12-2021-0451
|View full text |Cite
|
Sign up to set email alerts
|

No trust, no use: how young retail investors build initial trust in financial robo-advisors

Abstract: Purpose The purpose of this study is to describe and analyse the effect of a set of determinants on initial trust and behavioural intention to use financial robo-advisors (FRAs). Design/methodology/approach The theory of perceived risk and the behavioural finance paradigm were used to develop a conceptual model of retail investors’ initial trust in FRAs. Data collected from 554 young retail investors (YRIs) from Sweden and Malaysia were analysed using structural equation modelling. Findings The results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 81 publications
0
9
0
Order By: Relevance
“…Moreover, in this era, Fintech is recognized as one of the most agile, flamboyant, and engaging segments of the financial services marketplace (Ali et al, 2018). Similarly, Nourallah (2023) claimed that Fintech solutions gained more popularity in the fourth stage of the industrial revolution and after 2008. Schueffel (2016) applied semantic analysis of 13 peer-reviewed definitions of Fintech and defined it as "a new financial industry that applies technology to improve financial activities" (p. 32).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in this era, Fintech is recognized as one of the most agile, flamboyant, and engaging segments of the financial services marketplace (Ali et al, 2018). Similarly, Nourallah (2023) claimed that Fintech solutions gained more popularity in the fourth stage of the industrial revolution and after 2008. Schueffel (2016) applied semantic analysis of 13 peer-reviewed definitions of Fintech and defined it as "a new financial industry that applies technology to improve financial activities" (p. 32).…”
Section: Introductionmentioning
confidence: 99%
“…The literature emphasizes the significance of consumer age and technological competences [27], as well as financial knowledge, literacy and experience [28][29][30]. Some studies demonstrate the importance of trust in the technologies used in robo-advisory and the providers of robo-advisory [4,[31][32][33][34][35][36], as well factors related to risk acceptance [37][38][39]. Limitations to the acceptance of robo-advisory services were also pointed out, related to reluctance to make decisions made by machines, especially when they contain an ethical component [40].…”
Section: Introductionmentioning
confidence: 99%
“…Accountants recognize the relevance of blockchain in their job as well as its favorable impact on performance.In the research paper "Blockchain technology acceptance by investment professionals a decomposed TPB model" by Kumari and Devi (2022), the decomposed theory of planned behavior model is investigated using structural equation modeling. Findings revealed that DTPB provides the best fit for the data (Kumari and Devi, 2022).In the research paper "No trust, no use: how young retail investors build initial trust in financial robo-advisors" by Nourallah et al (2022), a set of determinants on initial trustThe author would like to express sincere gratitude to Professor Khaled Hussainey and Professor Aziz Jaffar for their invaluable guidance and support throughout the editorial process of this special issue. Their expertise and feedback have been instrumental in ensuring the quality and relevance of the articles included in this issue, and the author is grateful for their dedication to promoting the advancement of knowledge in the field of digital accounting and information technology.…”
mentioning
confidence: 99%
“…In the research paper “No trust, no use: how young retail investors build initial trust in financial robo-advisors” by Nourallah et al (2022), a set of determinants on initial trust and behavioral intention to use financial robo-advisors are suggested. Results revealed that the amount of public information, social media, information seeking and a rational decision-making style are positively associated with FRAs.…”
mentioning
confidence: 99%
See 1 more Smart Citation